2021
DOI: 10.3390/insects12110956
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Enhancement of Musca domestica L. 1758: Egg Load as a Measure of Optimal Larval Density

Abstract: The amount of waste produced by the population creates general health problems in terms of public health and hygiene. In recent years the common housefly (Musca domestica L. 1758; Dipteran: Muscidae) has been widely used in the treatment of organic wastes. This study aims to assess the effect of egg loading of the common housefly on maggot development and waste reduction. Housefly larvae were reared at four egg loads (1.25, 2.5, 5, 10 mg) under three different diets (wheat bran, millet bran, cow dung). Two-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…The amount of waste produced by residents raises general health problems in terms of public health and hygiene (Leyo et al, 2021). Several species of flies are used for recycling organic waste, including Hermetia illucens.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of waste produced by residents raises general health problems in terms of public health and hygiene (Leyo et al, 2021). Several species of flies are used for recycling organic waste, including Hermetia illucens.…”
Section: Resultsmentioning
confidence: 99%
“…Bran and blood; Millet bran, wheat bran, and cow dung (70% humidity adjusted by adding tap water to dry substrates); Poultry, pig, and cow manure, garbage, food scrapes, concentrated pig slurry; Maze bran Water and a mixture of sugar and powdered milk; A mixture of powdered milk and granulated sugar, water; A liquid formula, including water, sugar, milk, and other ingredients not reported; Honey, a mixture of 50% dry milk and 50% sugar. Fruit: banana, pineapple and papaya [ 22 , 63 , 67 , 193 , 194 ] Philornis downsi Dodge and Aitken Research for pest control Chicken blood, or chicken blood added with hydrolyzed protein, milk powder, or brewer’s yeast A diet consisting of water, ripe papaya, sugar, hydrolyzed protein, and milk powder [ 195 ] Stomoxys calcitrans (L.) To produce healthy individuals for experimentation. Research on pest control; Conduct research to establish alternatives of parasite control methods; A mixture of wheat bran, wood shavings, fish meal, ammonium bicarbonate and water; Alfalfa hay and water; A mixture of crushed dry dog food, beer yeast and blood meal, mixed with vermiculite Bovine blood with sodium citrate tribasic dihydrate and water; Citrated equine blood, plus a mixture of brown sugar mixed with tap water; Bovine blood [ 196 , 197 , 198 ] Sarcophagidae Agria housei Shewell Parasitoid–Biocontrol against lepidopteran pests Media based on salmon and fresh liver Not indicated [ 64 ] Boettcherisca peregrina Robineau-Desvoidy Waste treatment.…”
Section: Table A1mentioning
confidence: 99%
“…Several studies have also reported on the use of food waste and other waste products as a house fly substrate (Niu et al, 2017;Gao et al, 2019; (Qi et al, 2019;Eddy et al, 2021;Hamidou Leyo et al, 2021). Whereas these studies indicate that these substrates can be highly suitable the ingredients used often lack a suitable description, which hampers a good interpretation of the data.…”
Section: Manure Bioconversionmentioning
confidence: 99%